INFORMATION TECHNOLOGY AS A TOOL AND ENGINE OF TRANSLATION PRACTICE (American Journal of Technology and Applied Sciences, 2025)
The article explores the transformation of the translator's profession in the context of rapid advancements in information technology. The author analyzes the impact of tools such as machine translation systems, Translation Memory, and translation management systems on translation quality, speed, and efficiency. It is emphasized that information technologies have evolved from auxiliary tools into an integral part of a translator’s workflow, expanding professional capabilities and increasing competitiveness. At the same time, the article underlines that technology does not replace linguistic expertise but serves as a powerful instrument in the hands of a qualified professional.